Prevalência de hipertensão arterial em servidores universitários do Noroeste do Paraná - Marques, Angélica Sbrolini (2012)
Hypertension is one of the most important modifiable causes of premature cardiovascular morbidity and mortality in the world population, in addition to being an independent risk factor for cardiovascular disease. To assess the prevalence of hypertension in university. This is a cross-sectional study. Developed on 276 servers of both sexes, aged over 18 years at a university in northwest Paraná. Data collection was performed in 2011 by means of charts. The variables analyzed were: Cargo (Professor and Technical), length of service, gender and age. The biological variable was analyzed with hypertension (for definition of hypertension was used VI Brazilian Guidelines on Hypertension, values: SBP ≥ 140 and / or DBP ≥ 90). For statistical analysis we used SPSS 15.0. The prevalence of hypertension was statistically significant when associated with length of service in the institution over 20 years old (OR = 1.86, 95% -1,009-3,497, p = 0.04) and for age over 45 years (OR = 1.86, 95% CI - 0.994 to 3.497, p = 0.04). The prevalence of hypertension was positively associated with risk factors along with the old time in the institution. Thus the accession of a healthy lifestyle such as physical exercise and dietary control may determine improvements in BP values. Information devices and health-promoting the institution can improve the health profile of the servers.